1985
DOI: 10.1128/mcb.5.11.3274
|View full text |Cite
|
Sign up to set email alerts
|

The FLP recombinase of the Saccharomyces cerevisiae 2 microns plasmid attaches covalently to DNA via a phosphotyrosyl linkage.

Abstract: The FLP recombinase, encoded by the 2,um plasmid of Saccharomyces cerevisiae, promotes efficient recombination in vivo and in vitro between its specific target sites (FLP sites). It was previously determined that FLP interacts with DNA sequences within its target site (B. J. Andrews, G. A. Proteau, L. G. Beatty, and P. D. Sadowski. Cell 40:795-803, 1985), generates a single-stranded break on both DNA strands within the FLP site, and remains covalently attached to the 3' end of each break. We now show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…The spacer has no direct FLP protein contacts within the central 6 bp (3, 25). The DNA is cleaved at the spacer boundaries, with FLP forming a 3'-phosphotyrosine intermediate (8). Sequence alterations in the spacer that maintain these sequence features are generally well tolerated by the system, with some constraints (26).…”
mentioning
confidence: 99%
“…The spacer has no direct FLP protein contacts within the central 6 bp (3, 25). The DNA is cleaved at the spacer boundaries, with FLP forming a 3'-phosphotyrosine intermediate (8). Sequence alterations in the spacer that maintain these sequence features are generally well tolerated by the system, with some constraints (26).…”
mentioning
confidence: 99%
“…It was observed that such plasmids always had segregated plasmid clones having the Sal/SalI and +/+ arrangements on the inverted VOL. 8,1988 on May 11, 2018 by guest http://mcb.asm.org/ Downloaded from repeats with significantly high frequencies, except for pSRT327 (R-), pSRT0609, and pSRT0627, each of which had a defect in the intramolecular recombination by disruption of the R gene or a deletion at the 58-bp region (Table 1). (Chimeric plasmid pSRT0627 has one exceptional clone exhibiting gene conversion, but it may be due to the gene conversion mechanism of the host cell).…”
Section: Resultsmentioning
confidence: 99%
“…8), indicating that the enzyme exhibits mechanistic similarities to integrase and Flp recombinase. These enzymes belonging to the integrase family of site-specific recombinases (36) bind covalently to the 3Ј-phosphoryl of the cleaved strand via a phosphotyrosyl linkage (37,38). Three short motifs named box A, B, and C conserved in these proteins (36) are also present in TelN.…”
Section: Discussionmentioning
confidence: 99%